Critical Synthesis Package: Inventory of General Study Orientations (IGSO) - Jane Rosenthal (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the Inventory of General Study Orientations (IGSO), and (2) a copy of the IGSO instrument and the IGSO factor loadings developed by Erkki Olkinuora, MEd. The IGSO is a survey for ascertaining students' general study orientation, which includes subscales for personal meaning they find in their studies. This is a 35 Likert-scaled item questionnaire, subdivided into 8 factors consisting of: Lack of interest, Achievement (desire to achieve), Social, Work-Life, Deep Learning, Surface-Anxiety, Systematic, and Practical. This measure may be a useful in looking holistically at students' educational values. The instrument has been used with undergraduate and medical students in Finland. A strength of the IGSO is that it focuses on general study orientations that seem independent of contextual or environmental influences and has shown adequate reliability in previous studies. A disadvantage of this inventory is that some specific items demonstrated low reliability as related to the construct being measured. An additional disadvantage of the IGSO is that it has only been utilized with students in Finland and has not been shown to be valid or reliable with students in other countries using the English translation.